Reduction of surgical-site infections and improvement of scar parameters with a uniform fractional ultra-pulse CO₂ laser protocol in cosmetic surgery: a five-center retrospective cohort - Xu, Qinghua; Li, Haoran; Zhao, Juhui; He, Xiao; Zhao, Liliang; Zhang, Xiaofeng (Frontiers in Medicine, 2025)
BackgroundPostoperative infections and suboptimal scar outcomes remain persistent challenges in cosmetic surgery, impairing patient satisfaction and quality of life. This study evaluates whether a standardized fractional ultra-pulse CO₂ laser regimen can mitigate these complications.MethodsA multicenter retrospective cohort enrolled 562 adults undergoing elective rhinoplasty, liposuction, breast augmentation, facelift, abdominoplasty, or Botox. Laser eligibility (incision >3 cm, Fitzpatrick I–IV, no collagen-vascular disorder) was determined by an EMR-embedded checklist; 324 patients received a uniform three-stage laser protocol (pre-incision, immediate post-closure, day 10). All patients followed a five-day antibiotic regimen (oral cefalexin + topical mupirocin). Baseline covariates were balanced via IPTW. SSIs were microbiologically confirmed (aerobic, anaerobic, fungal, mycobacterial cultures with MALDI-TOF). Comparative analyses used Welch’s t-test and Fisher’s exact test; infection-free survival was assessed by Kaplan–Meier curves, and IPTW-adjusted Cox models quantified laser effects on SSI risk.ResultsOf 562 patients, 324 (58%) received laser therapy. Baseline demographics and comorbidities were balanced across groups (all p > 0.05). Laser-treated patients had faster healing (13.8 ± 5.7 vs. 17.0 ± 3.2 days; p < 0.001), lower CRP (11.3 ± 7.4 vs. 14.9 ± 4.4 mg/L; p < 0.001), thinner scars (2.44 ± 1.39 vs. 3.14 ± 0.78 mm; p < 0.001), and greater elasticity (0.85 ± 0.03 vs. 0.65 ± 0.03 AU; p < 0.001). Pigmentation, vascularity, and collagen III/I ratios were all significantly improved (p < 0.001). SSIs were reduced (15% vs. 59%; p < 0.001), as were keloids (1.9% vs. 11%; p < 0.001). Satisfaction, quality-of-life scores, and return to activity favored the laser group (all p < 0.001). Kaplan–Meier curves confirmed superior 30-day infection-free survival (log-rank p < 0.001); IPTW-adjusted Cox regression showed a 72% reduced infection hazard (HR = 0.28; 95% CI: 0.19–0.41; p < 0.001).ConclusionStandardized fractional ultra-pulse CO₂ laser therapy reduces SSIs, improves scar outcomes, and enhances patient satisfaction in cosmetic surgery. These findings support wider adoption of laser protocols, warranting further prospective, pathogen-specific research.